Information technology and organisational performance: An integrative model of IT business value - Success, Obieze Ewere (International journal of economic perspectives, 2022)
Managing Information Technology (IT) investments continues to be a challenge for firms due to the difficulty associated with demonstrating IT contributions to organisational performance. Many IT contributions are not accounted for because they cannot be easily quantified. Linking IT to organisational performance is a complex problem that is informed by insights from multiple theoretical paradigms. This paper aims to comprehensively review work done by both academics and practitioners and to explore why new approaches to managing IT investments are needed. To achieve this aim, we will start by defining IT assets and business value and exploring the different dimensions used to measure the business value of IT. Then, we will look at the early research on IT business value and the emergence of the Productivity Paradox. After that, we will delve into the three current theoretical paradigms: economics, management and sociology. The theoretical lenses and models used in these paradigms will also be discussed. Finally, future research directions are suggested.